2002
DOI: 10.1093/humrep/17.4.1101
|View full text |Cite
|
Sign up to set email alerts
|

Association of polymorphisms of the oestrogen receptoralpha gene with the age of menarche

Abstract: We document that the XbaI polymorphism, and possibly PvuII, may be genetic determinants of the age of menarche.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
78
3
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(86 citation statements)
references
References 27 publications
3
78
3
2
Order By: Relevance
“…Age at menarche is also influenced by genetic factors. XbaI polymorphism of estrogen receptor alpha gene was proved to be associated with combined predisposition to AIS occurrence, curve severity, and late menarche, which strongly mirrors the findings of our study [18][19][20].…”
Section: Discussionsupporting
confidence: 90%
“…Age at menarche is also influenced by genetic factors. XbaI polymorphism of estrogen receptor alpha gene was proved to be associated with combined predisposition to AIS occurrence, curve severity, and late menarche, which strongly mirrors the findings of our study [18][19][20].…”
Section: Discussionsupporting
confidence: 90%
“…38 Therefore, the ER-a gene has been considered as a candidate gene for the onset of menarche, which was substantiated in several studies. 39,40 Another possible pleiotropic gene is beta 3-AR gene. Mutations in beta 3-AR gene may result in a diminished lipolytic response in adipose tissue and lower resting metabolic rate.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, correlative epidemiological studies have identified the early onset of regular ovarian cycles after menarche as a risk factor (Apter & Vihko, 1983). Moreover, two different polymorphisms of the estrogen receptor a gene, which are associated with reduced breast cancer risk, were also associated with a relative delay in menarcheal age in Greek adolescent girls (Stavrou, Zois, Ioannidis, & Tsatsoulis, 2002). From literature on adult menstrual cycle function, we know that the timing and incidence of pregnancy, lactation, and menopause all confer risk or protection from breast cancer (Hilakivi-Clarke et al, 2002;Kelsey, 1989;Pike et al, 1993).…”
Section: Introductionmentioning
confidence: 99%